Teaching Translation Using E- Learning During the Time of COVID-19 Pandemic: Yemeni Universities as a Case in Point - Ahmed Mohammed Ahmed Moneus (Applied Information Technology And Computer Science, 2022)
This paper sheds light on using open learning or distance learning in teaching translation during the crisis in Yemen. The paper aims to identify the role of electronic learning in teaching translation in Yemen during crisis. This paper discusses several successful initiatives in using E- learning/ open learning in Yemen. Two of Yemen’s most prestigious universities were nominated to be examined. The public University of Sana’a and the private University of Science and Technology are both located in Sana’a. Ten professors of translation volunteered to participate in the semi structure interview. The findings show that open learning provide a new way to teaching translation during crisis, student would be able to learn and study translation in easy way, despite the problems that teachers experience, such as the Yemeni network’s instability and a lack of proper equipment for high-tech e-learning. Recommendation was presented towards more focusing on using open learning in teaching translation.